Emotional Harmony: Strategies for Building a Prosperous and Happy Buddhist Family (HITA SUKHAYA) - Suryani, Suryani; Nyanasuryanadi, Partono; Surya, Julia (International Journal of Religion Education and Law, 2024)
Humans as social creatures need interaction and depend on each other. So that this interaction can be in line with each individual, a group is formed. Family is the smallest group in life. A family is formed from a household life, but married life is a choice in Buddhism, so when the choice falls on married life it is necessary to pay attention to strategies to create a happy and prosperous family. Building a household is the same as building a house, a strong foundation is needed so that the house can stand firmly, likewise, with the right foundation for a household, a harmonious, prosperous and happy family will be created. When marriage is no longer just about two people but two families, uniting two individuals who may have different characters and emotions is not easy, let alone two families. For this reason, it is necessary to understand the right strategy to create harmony in household life based on Buddhist teachings. The method for this writing is qualitative with a descriptive approach through various literature studies. In this article, we will explain everything from self-preparation in choosing the right partner to make it easier to take further steps, understanding the nature of marriage to be more confident in carrying out domestic life, and also the economy which is a generator of prosperity which is quite a topic of disharmony in the household. at this time. There is great hope that after understanding all of these concepts, Buddhists who choose to live as married people can create a prosperous, happy and harmonious Buddhist family based on Buddhist teachings (Hita Sukhaya)